(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Arun Joshi, winner of the Sahitya Academy Award in 1983,is one of the distinguished Indian English novelists. His fiction delineatesthe modernity of human condition and explores some fundame4ntal problems ofhuman existence. His fictional world marks a serious attempt at disentanglingthe convoluted maze, Joshi’s metaphor for life with its complexity andinexplicable mystery. In fact, he is writer by choice and a management expertby training and profession.